Analyzing gender and age differences in travel patterns and accessibility for demand response transit in small urban areas: A case study of Tennessee - Jing Guo; Sabyasachee Mishra; Candace Brakewood (Journal of Transport and Land Use)
Demand Response Transit (DRT) services (e.g., dial-a-ride) play a crucial part in supporting transportation systems in small urban and more rural areas. However, the exploration of DRT trip patterns and accessibility, particularly the differences tied to demographics such as gender and age, remains an underdeveloped field. This study begins to fill this research gap by statistically and spatially analyzing real-world DRT trip data from Tennessee. DRT trip purposes were identified based on origin and destination land uses. Statistical analysis was conducted to evaluate DRT travel patterns for passengers of different demographic groups, particularly women and the elderly. Spatial analysis identified areas with higher DRT trip demand and limited DRT accessibility as potential essential destination deserts. The results show that women took more DRT trips across all purposes (e.g., Home-Healthcare, Home-Home, and Home-Leisure) except for Home-Work. About 36.8% of the DRT trips were made by the elderly, primarily for Home-Healthcare trips (67%), and they preferred shorter DRT trips. Spatial analysis revealed disparities in potential essential destination deserts for the elderly and females, as well as differences in possible deserts by trip purpose (e.g., healthcare-related trips). This study contributes to the literature by proposing a methodological framework for assessing DRT travel patterns and accessibility, which has been excluded from most of the prior literature on accessibility.